2011
DOI: 10.1002/jemt.21001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of hydrophilic and hydrophobic ionic liquids for observing cultured human cells by scanning electron microscopy

Abstract: An ionic liquid (IL) is a salt that remains in the liquid state at room temperature. It does not vaporize under vacuum and imparts electrical conductivity to samples for observation by scanning electron microscopy (SEM). Recently, the usefulness of ILs has been widely recognized. In our previous study, one of the ILs 1-ethyl-3-methylimidazolium tetrafluoroborate (EtMelm(+) BF(4)(-)) was used for SEM analysis of biological samples. In comparison with the conventional method, samples prepared using EtMelm(+) BF(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…These FE-SEM results indicate that fine morphologies can be clearly observed using hydrophilic IL without any conductive coating. Ishizaki et al have reported that a simple technique using hydrophilic IL enables the observation of the fine thread-like morphologies of cultured human cells [28]. In good agreement with this report, we observed fine morphologies of filamentous fibrils using an IL.…”
Section: Morphological Observation Of Biofilm Formationsupporting
confidence: 92%
See 1 more Smart Citation
“…These FE-SEM results indicate that fine morphologies can be clearly observed using hydrophilic IL without any conductive coating. Ishizaki et al have reported that a simple technique using hydrophilic IL enables the observation of the fine thread-like morphologies of cultured human cells [28]. In good agreement with this report, we observed fine morphologies of filamentous fibrils using an IL.…”
Section: Morphological Observation Of Biofilm Formationsupporting
confidence: 92%
“…On the other hand, the observation of biological materials by electron microscopy without structural deformation is a real challenge. In this regard, combining ILs with biological materials can be the most simple and attractive approach to reveal the morphological structure by electron microscopy [27,28]. We found that the osmotic pressure of biological materials needs to be maintained to observe the fine morphology [29].…”
Section: Introductionmentioning
confidence: 96%
“…HeLa and A549 are most popularly used and well documented cell lines, from our previous studies, we have clearly understood the biogenesis of RBM8A and Upf2 in HeLa and A549 (Ishigaki et al, ; Ishigaki et al, ; Ishigaki, Nakamura, Tatsuno, Ma, & Tomosugi, ; Tatsuno & Ishigaki, ; Tatsuno, Nakamura, Ma, Tomosugi & Ishigaki, ). We performed immunostaining for Y14 and Upf2 in an ultrathin section for TEM as shown in Figure .…”
Section: Resultsmentioning
confidence: 82%
“…[17] Moreover, RTIL treatment can mitigate artifacts in biological samples such as wrinkling, shrinkage, and cracking, and it may provide a closer morphological representation of the natural hydrated microbe state. [17] Researchers have utilized RTILs purely as an alternative to metal sputter coating, [17][18][19][20] while others have used RTIL to image living bacterial cells and red blood cells with SEM. [21,22] While these studies have shown the capacity to image cells, they have often been limited to single endpoint studies on non-complex substrates with simple organisms such as bacteria.…”
Section: Introductionmentioning
confidence: 99%